The Role of Sport and Physical Education in Self –Concept Development of Children and Adolescents - Kalogiannis, Περικλής (Inquiries in Physical Education and Sport, 2006)
The positive effect of involvement in physical education and sports in the course of a normal and harmonious physical development of a child has already been established (Bailey et al., 1986; Bar-Or, 1983; Pangrazi, 1997; Tokmakidis & Douda, 1999). Moreover, it is also generally acceptable that it conduces to the psychological development of the child, contributing to the shaping of a multifaceted and harmonious personality (Fox, 1997; Whitehead & Corbin, 1997). With the acceptance of the multiple dimension of the self’s structure, the opportunity was given for research into the physical self as a separate unit. The development of suitable psychometric tools facilitated the measurement of physical self-concept. Abundance of research results has proven the positive correlation between participation in programs of physical activity and higher levels of physical self-esteem and global self-concept. Furthermore, there are research findings that children with high indices of body composition and low level of physical fitness manifest lower physical self-esteem and perceived competence, decreased motivation, negative attitudes towards Physical Education exercise settings and show higher anxiety levels when they are involved in physical activities. The appropriate teaching of Physical Education can help children form an objective image of their physical self and acquire a positive physical self-esteem, which will allow them to participate actively in sports and physical activity programs and to experience the lifelong benefits of this participation.